POTENSI TAMAN BUAYA INDONESIA JAYA SEBAGAI DAYA TARIK WISATA EDUKASI DI BEKASI - Ufairah Wafa; Priyanto . (Eduturisma, 2021)
Abstract The development of tourism, especially educational tourism, is currently increasing. This increase is characterized by the emergence of various tourist activities, which are supported by various facilities and services provided by community elements, and entrepreneurs, as well as the government of both the central and local governments. This study examined the educational tourism activities of Taman Buaya Indonesia Jaya in Bekasi Regency, West Java. The existence of Taman Buaya Indonesia Jaya in Bekasi Regency is able to become a research center and learning and learning resource, which is expected to improve the competence of educators and learning insights in seeking to improve the quality of education, as well as become an educational tourism destination. Educational tourism activities include: conferences, research, student exchanges both on a national and international scale, school visits, language schools, and study tours, which are formally and non-formally organized, in the form of natural and artificial tourism. Forms of learning about history, geography, language, religion, and culture, through important site visits, in the future have the potential to be further developed in order to provide benefits for stakeholders.